Severe Acute Respiratory Syndrome (SARS-CoV-2): A national public health emergency and its impact on food security in Peru (Scientia Agropecuaria, 2020)
On March 16, 2020, a policy of quarantine and social isolation initiated in Peru imposed by the declaration of National Public Health Emergency for Severe Acute Respiratory Syndrome (SARS-CoV-2), which is affecting everyone. The research aimed to collect information that anticipates the impacts on the quantity and the need to distribute food for food security. From a global point of view, fiscal, monetary, and macro-financial policies corresponding to approximately 7% of the National GDP. These efforts will be insufficient if they are not complemented by adequate planning to supply the needs of Peru with at least 484,402.1 kilos of food per month, concerning agricultural products contained in the index basket and that need to be distributed in all regions of the country, such as rice, potatoes and at least 14 other products. In conclusion, measures in four aspects are urgent: technological, scientific, humanitarian, and planning, in addition to those implemented, to mitigate the impacts on food security, now and post-pandemic, it is suggested that the issue should be treated from a transdisciplinary perspective.